Fuel Conversion Benefit of Producer Gas over Gasoline – An Experimental Analysis. (November 2016) - Babu, M.S.; Clement, S.; Rajan, N.K.S.
Abstract: Growing energy targets, depletion of fossil fuels and environmental concerns have paved the way to explore alternative (renewable) fuels. In this paper, the performance and in-cylinder analysis of a four stroke modified spark ignition engine fueled with bottled Producer gas is addressed. The nature of energy conversion of a producer gas (a multi component fuel) as compared to straight-run Gasoline was analyzed and discussed. Study shows that, Producer gas engines can yield a saving of approximately over 70% on fuel consumption over Gasoline powered engines. Analysis of fuel conversion indicated a scope of reduced energy consumption with producer gas engine to the tune of 5%.